2012
DOI: 10.1097/ccm.0b013e3182657560
|View full text |Cite
|
Sign up to set email alerts
|

G-protein coupled estrogen receptor 1 mediated estrogenic neuroprotection against spinal cord injury*

Abstract: These results reveal that G-protein coupled estrogen receptor 1 may mediate estrogenic neuroprotection against spinal cord injury, and underline the promising potential of estrogen with its new target G-protein coupled estrogen receptor 1 for the treatment of spinal cord injury patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Some researchers have raised the possibility that some modifiers that reside on the X chromosome may affect the phenotype [36]. The high level of oestrogenic hormone in women was also speculated to be associated with neuroprotection [37,38,39]. Further studies on the mechanism of gender difference in SPG4 may provide a clue for HSP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have raised the possibility that some modifiers that reside on the X chromosome may affect the phenotype [36]. The high level of oestrogenic hormone in women was also speculated to be associated with neuroprotection [37,38,39]. Further studies on the mechanism of gender difference in SPG4 may provide a clue for HSP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, GPR30 is mainly distributed in the motoneurons of the ventral horn and white matter of the spinal cord [17], both of which are directly associated with motor function. The tissue distribution characteristics of GPR30 led to the hypothesis that GPR30 might be a candidate for promoting recovery of SCI-induced motor dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by this group confirmed that estrogen exerts a neuroprotective effect following SCI, via GPR30 (18). It was hypothesized that apoptosis within the spinal cord may increase following SCI, and that estrogen administration may decrease this apoptosis.…”
Section: Discussionmentioning
confidence: 69%
“…In a previous animal study by this group, it was observed that apoptosis in the spinal cord increases in the early stages following SCI (18). It has been reported in a number of previous studies that estrogen may exert an antiapoptotic effect following SCI by enhancing antiapoptotic gene expression, while reducing caspase-3 activity and inhibiting calcium activation (21,3537).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation